2017
DOI: 10.1038/cddis.2017.493
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 and miR-145 inhibit gastric cancer cell migration and metastasis by suppressing MYO6

Abstract: Metastasis is a major clinical obstacle responsible for the high mortality and poor prognosis of gastric cancer (GC). MicroRNAs (miRNAs) are critical mediators of metastasis that act by modulating their target genes. In this study, we found that miR-143 and miR-145 act via a common target gene, MYO6, to regulate the epithelial–mesenchymal transition (EMT) and inhibit metastasis. We determined that miR-143 and miR-145 were downregulated in GC, and the ectopic expression of miR-143 and/or miR-145 inhibited GC ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 42 publications
7
84
0
Order By: Relevance
“…Nowadays, a growing body of studies have revealed that miRNAs are involved in DNA damage and repair, apoptosis regulation, cell cycle regulation and so on [18]. Chao Lei et al found that miR-143 and miR-145 inhibited GC cell migration and metastasis by inhibiting MYO6 expression and EMT [19]. Rui Ye et al verified that miR-195 overexpression could prolong the life of patients with gastric tumor by enhancing cisplatin chemo sensitivity [20].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a growing body of studies have revealed that miRNAs are involved in DNA damage and repair, apoptosis regulation, cell cycle regulation and so on [18]. Chao Lei et al found that miR-143 and miR-145 inhibited GC cell migration and metastasis by inhibiting MYO6 expression and EMT [19]. Rui Ye et al verified that miR-195 overexpression could prolong the life of patients with gastric tumor by enhancing cisplatin chemo sensitivity [20].…”
Section: Introductionmentioning
confidence: 99%
“…But in recent years, it has been estimated that more than 60% of human protein-coding genes are regulated by miRNAs. 13 The importance of miR-145 in the pathogenesis of RA has been mentioned by several researchers. With regard to RA, miRNAs may serve as potential biomarkers for both diagnosis and prognosis for RA, 5 with, in particular, evidence for miR-146a/b upregulation in RA synovial tissue, 6 and miR-125 upregulation in peripheral blood mononuclear cells and plasma posttreatment.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43] Earlier studies suggested that MIR143-3p can inhibit cell migration and epithelial-mesenchymal transition. 44,45 We report that MIR143-3p reconstitution not only inhibits GC cell proliferation and gastric organoid growth but also sensitizes cancer cells to CDDP treatment. Our results show BRD2 as a novel direct downstream target of MIR143-3p.…”
Section: Discussionmentioning
confidence: 98%